RANCANG BANGUN ANTENA HEXACULA OMNIDIREKSIONAL STRIP KEMBAR BINOMIAL 0,3GHz-3,0GHz, VSWR ≤ 2, BERTERMINAL 50Ω SMA, BERCATUAN MONOPOL - Safwan (J-Innovation, 2015)
The wireless communication technology is grow up very fast and varied. The transmission equipment, andantenna will be effected by it. At this time many applications work in frequency band 0.3 GHz - 3.0 GHz,such as television, GSM, CDMA, and WiMAX. However, its used one-antenna for one technology. So weneed an antenna that can solve this problem, the Hexacula omnidirectional antenna will created to solvethis problem. After measured in laboratorium of microwave and in environment of ITTelkom, operatingfrequency 736.2 MHz-3000Mhz in VSWR≤1.5 and 600MHz-3000MHz in VSWR ≤2.0, Omnidirectional,Ellips Polarization, gain 6,353±1,428 dBi and the average impedance is 52.00821+j8.46. The result ofmeasurement already achieve the specification except operating frequency and polarization. If want toachieve the oprating frequency as the specification, suggestion are make a smaller slice in upper stripsfrom 2mm to 0.1mmand make conic higher than before that is from 3.1cm to 5.0cm. If want to achieve thepolarization as the specification, suggestion are use the pencil beam antenna when measure thepolarization and dielectric size must be match with width strips.